=\(\frac{1}{3}\left(\frac{1}{4}-\frac{1}{7}\right)+\frac{1}{3}\left(\frac{1}{7}-\frac{1}{10}\right)+..........+\frac{1}{3}\left(\frac{1}{97}-\frac{1}{100}\right)\)
=\(\frac{1}{3}\left(\frac{1}{4}-\frac{1}{7}+\frac{1}{7}-\frac{1}{9}+........+\frac{1}{97}-\frac{1}{100}\right)\)
=\(\frac{1}{3}\left(\frac{1}{4}-\frac{1}{100}\right)\)
=\(\frac{1}{3}x\frac{6}{25}\)=\(\frac{2}{25}\)
vậy biểu thức trên có giá trị bằng\(\frac{2}{25}\)
\(\frac{3}{1.4}+\frac{3}{4.7}+\frac{3}{7.10}+...+\frac{3}{97.100}\)
=\(1-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+\frac{1}{7}-\frac{1}{10}+..+\frac{1}{97}-\frac{1}{100}\)
= \(1-\frac{1}{100}=\frac{99}{100}\)
= 1/1-1/4+1/4-1/7+1/7-1/10+....+1/97-1/100
=1/1-1/100
=99/100
chắc chắn đúng cô giáo tôi cho làm bài này đến chục lần rồi